2022
DOI: 10.17507/tpls.1210.10
|View full text |Cite
|
Sign up to set email alerts
|

Online Scaffolding Strategies: Case Studies of Asian EFL Learners in an Academic Writing Course

Abstract: The article reported a case study investigating the scaffolding strategies of twelve Asian EFL learners in four small groups’ scaffolding strategies during two online collaborative writing (OCW) tasks in a composition course using Google Docs as a writing platform. Of interest was how EFL learners with different L1 scaffold each other while co-constructing OCW tasks, and also if scaffolding strategies used       during OCW tasks influence writing performance. Data collection included pre-test and post-test wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Moreover, Chu et al (2017) claimed that social media tools such as Wikis for collaborative groups can promote online collaborative and interactive learning in secondary students. Kitjaroonchai et al (2018) stated that Thai university students significantly improved their translation skills after learning through online collaborative learning (OCL) and had positive attitudes towards OCL. Moreover, Nam (2017) claimed that using digital storytelling strategies with middle school students in South Korea improved online communication and students' interaction in online collaborative learning environments.…”
Section: List Of Figures Pagementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Chu et al (2017) claimed that social media tools such as Wikis for collaborative groups can promote online collaborative and interactive learning in secondary students. Kitjaroonchai et al (2018) stated that Thai university students significantly improved their translation skills after learning through online collaborative learning (OCL) and had positive attitudes towards OCL. Moreover, Nam (2017) claimed that using digital storytelling strategies with middle school students in South Korea improved online communication and students' interaction in online collaborative learning environments.…”
Section: List Of Figures Pagementioning
confidence: 99%
“…In addition, Jeong (2019) revealed that the participants showed satisfaction in learning English through online collaborative learning. According to Klemm (1988), the use of technology tools significantly supported online collaborative learning and make it more effective than face-to-face collaborative learning for several reasons; provide flexible schedules, support students' responsible in learning, promote critical thinking, have more organized learning process. Thompson & Ku (2006) proposed four criteria of online collaborative learning which was participation, interdependence, synthesis of information, and independence.…”
Section: Online Collaborative Learningmentioning
confidence: 99%